2017
DOI: 10.1136/bmjopen-2017-017789
|View full text |Cite
|
Sign up to set email alerts
|

Burden of early-term birth on adverse infant outcomes: a population-based cohort study in Brazil

Abstract: ObjectivesTo estimate the national rate of early-term live births in Brazil and to evaluate the effect of birth at 37 and 38 weeks’ gestation, as compared with 39 and 40 weeks’ gestation on infant outcomes according to precursors of birth and the existence of maternal/fetal medical conditions.DesignNational perinatal population-based cohort study.Setting266 maternity services located in the five Brazilian macroregions.Participants18 652 singleton live newborns from 37 0/7 to 40 6/7 weeks of gestation.Main outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
2
43
2
9
Order By: Relevance
“…Because rates for moderate and late preterm births were combined, we only have partial data on the specific burden of late preterm birth. Only sparse data exist from lower-and middle-income countries on early term birth rates; Brazil reports 35% [33] and China between 23% and 29% among singleton live births [34]. This lack of information on the burden of early term delivery in lower-and middle-income countries constitutes an important limit to our knowledge.…”
Section: Prevalence Of Late Preterm and Early Term Birthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because rates for moderate and late preterm births were combined, we only have partial data on the specific burden of late preterm birth. Only sparse data exist from lower-and middle-income countries on early term birth rates; Brazil reports 35% [33] and China between 23% and 29% among singleton live births [34]. This lack of information on the burden of early term delivery in lower-and middle-income countries constitutes an important limit to our knowledge.…”
Section: Prevalence Of Late Preterm and Early Term Birthsmentioning
confidence: 99%
“…Our review of the literature shows that differences in indicated early deliveries are likely to explain part of the cross-country variation and that changes in medical practices constitute one lever for lowering preterm and early term birth rates. In countries where there is a relatively high proportion of early term births (> 30%), such as the USA, Portugal and Brazil, there has been a recent push by professional societies to reduce the number of elective obstetric deliveries before 39 weeks [23,33,72], and in the USA financial incentives are used to limit these births based on Medicaid policy [75]. It would be of interest to evaluate management strategies by comparing decision-making and indications for provider-initiated deliveries across countries with high and low rates of early delivery.…”
Section: Prevention From An International Perspectivementioning
confidence: 99%
“…However, women in the standard of care model presented almost twice the proportion of early term births, most of them associated with antepartum cesarean sections. It is estimated that, in Brazil, about 35% of live births are early term 31 , corresponding to more than 300 thousand early term births per year, with a higher prevalence in places with cesarean rates above 80% 32 . In a previous nationwide Brazilian study, early term births, especially non-spontaneous births, were associated with several negative outcomes, such as oxygen use, neonatal ICU admission and neonatal death 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The finding was highly relevant, since these children were shown to be at increased risk of negative outcomes such as oxygen use, neonatal ICU admissions, hypoglycemia, respiratory problems, jaundice, and delays in breastfeeding, especially in neonates born by prelabour cesarean sections 6 . The Federal Board of Medicine issued a crucial resolution (Resolution CFM n. 2,144/2016) according to which cesareans in normal-risk pregnancies can only be performed at 39 weeks' gestational age or greater 7 , in line with the decision made by the American College of Obstetrics and Gynecology (ACOG) in 2013 8 .…”
Section: Childbirth and Birth In Brazil: An Evolving Scenariomentioning
confidence: 98%